(untitled) (Economic and Political Thought, 2012)
There is no doubt that, as a result of the public finance crisis in all the Euro zone countries and also some other European Union member states, the European Union institutions once again strive to confirm their reliability both in Europe and on the global arena. The Treaty of Lisbon, which is being implemented, built formal foundations of changes that are aimed at that direction. It provides that the European Citizens’ Initiative will be introduced, there will be a change in the European Parliament election system and national parliaments will be given more rights in the European Union decision-making process. Special attention should be paid to sparing no effort to show the European Union citizens that the European Union can be a real and effective formula for finding remedies for the crisis. The stakes are high in this game. In fact, it is the question regarding the future of the European integration, i.e. whether it will be the Union of strengthened political cooperation around home market and the Euro zone or the Union weakened by conservative nationalism focusing on suggestions made in some states that it is necessary to search for alternative to the European ways of fighting against the crisis.